A comparative historical study of swimming and paralympic athletics participations and competitions for the period from 1960-2024 - Hamza, Jamal; Ibrahim , Mohamed; Jawad , Ali (Journal of Physical Education, 2025)
The Paralympic Games is a major global sporting event and is a special gathering of a group of society who have been psychologically and physically rehabilitated to represent their countries in various sports  The aim of the research  is - Document the historical trajectory of the quantity and diversity of swimming and Paralympic athletics competitions at the Summer Paralympic Games during the period from 1960 to 2024 - Compare and analyze the quantitative evolution of athletes' and countries' participation in both swimming and Paralympic athletics across different cycles. The researchers used the descriptive, comparative analytical approach, the research community consisted of (all competitions, results and participation of athletes and countries in swimming and athletics in all summer Paralympic Games held during the period from 1960 (Rome Games) to 2024 (Paris Games). This includes all approved events, the number of participating athletes (males and females, and of different categories of disability), and the number of countries represented. Main Conclusions Both sports have witnessed tremendous and continuous growth in the number of male and female athletes and participating countries over sixty years, underscoring their position and their significant role in the development of the Paralympic movement – yet athletics excels in all the data studied, indicating greater flexibility in logistical requirements and a wider diversity of opportunities to participate compared to swimming, which requires more specialized and expensive infrastructure and equipment. The most important recommendations are that the officials of the Paralympic Committee should provide all the main support requirements for developing countries to establish and develop all the requirements of swimming to promote wider participation in it.